2019
DOI: 10.3389/fninf.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technological Solutions for Assessment, Treatment, and Assistance in Mild Cognitive Impairment

Abstract: Alzheimer's disease, and dementia, represent a common cause of disability and one of the most relevant challenges in the health world. In addition, these conditions do not have, at moment, a pharmacological treatment that can stop the pathological progress. Mild cognitive impairment (MCI), defined as the borderline between normal aging and early dementia, represents a meaningful field of study because, in the transition to dementia, clinicians have defined a useful therapeutic window. Additionally, due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“… Holgado et al (2019) reported an impairment in accuracy and reaction time with a high cognitive load (2-back) compared to a low cognitive load (1-back) despite no impairments in power-output (217 W:222 W) and RPE during a 20 min self-paced cycling time-trial. Moreover, numerous studies have reported a decline in visual attention when mental load is increased which corresponds with the findings in the current study ( Hancock and McNaughton, 1986 ; Vickers et al, 1999 ; Pesce et al, 2003 ; Bundesen et al, 2005 ; Diekfuss et al, 2017 ; Mancioppi et al, 2019 ). The accumulation in mental fatigue with multiple feedback as the exercise progressed resulted in a lower average power-output (227.99 ± 42.02 W) compared to single feedback (287.9 ± 60.07 W; Figure 2 ).…”
Section: Discussionsupporting
confidence: 91%
“… Holgado et al (2019) reported an impairment in accuracy and reaction time with a high cognitive load (2-back) compared to a low cognitive load (1-back) despite no impairments in power-output (217 W:222 W) and RPE during a 20 min self-paced cycling time-trial. Moreover, numerous studies have reported a decline in visual attention when mental load is increased which corresponds with the findings in the current study ( Hancock and McNaughton, 1986 ; Vickers et al, 1999 ; Pesce et al, 2003 ; Bundesen et al, 2005 ; Diekfuss et al, 2017 ; Mancioppi et al, 2019 ). The accumulation in mental fatigue with multiple feedback as the exercise progressed resulted in a lower average power-output (227.99 ± 42.02 W) compared to single feedback (287.9 ± 60.07 W; Figure 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Despite this rapid evolution, or perhaps because of this high pace of development, this state of the art has yet to result in wide adoption of digital approaches in aging research beyond rather narrow focused use of various wearables or apps. Prior smart home or pervasive computing platforms for aging research have demonstrated the feasibility and potential of such platforms to uniquely inform research [9][10][11][12][13][14][15]. However, several barriers to their proliferation have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Many specific technologies and uses of remote monitoring have been developed to advance aging research [e.g., [5][6][7][8]. These advances have tended to benefit a relatively small community of specialty research; the broader gerontological research communities have not seen more widespread uptake of these methods, despite the demonstrated feasibility and potential of smart home and pervasive computing platforms to uniquely inform aging research and healthcare of older adults [9][10][11][12][13][14][15]. A number of barriers have prevented sensor-based and remote monitoring research from becoming ubiquitous: technical challenges, a lack of standards, team science requirements and lack of specialty expertise, narrow real-world use cases, proprietary algorithms and other access-limiting intellectual property rights, and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies emphasized the integration of ICT and assistive technology in the social integration of visually impaired people (Agree, 2014;Katerina Mavrou et al, 2017). Several studies also cautioned that the effectiveness of ICT on the betterment of life of visually impaired people is subject to compatibility of assistive technology with ICT devices (Archer et al, 2014;Hakobyan et al, 2013;Hollier, 2017;Mancioppi et al, 2019). These factors exacerbate the digital divide among the students with visual impairment.…”
Section: Review Of Literaturementioning
confidence: 99%